Uma sequência didática sobre o ensino da evolução biológica a partir de uma perspectiva histórica - Alves, Ildicely de Oliveira (2019)
This work is the result of some reflections about the teaching of the “origin and evolution of life” in Basic Education in a research developed with the Professional Master’s Degree in Teaching Biology. In the context of the classroom, the teachers face some hindrances when working with the theme, such as conceptual difficulties, sociocultural matters and didactic strategies that contribute to the comprehension of the key concepts of evolutionary theory. The proposal of the thesis was the elaboration and application of a didactic sequence with dynamic, attractive and meaningful classes, aiming to deepen the reflections about the evolutionary theory, in a historical context, recurring to geological times and to the history of life in the Earth. As a guiding principle of this didactic intervention, the Socioconstructivism Learning Theory of Vygotsky presents itself as fundamental. In the didactic sequence, we presented a suggestive overview of the classes about the biologic evolution, considering the history of life in Earth.